PENGARUH VARIASI TEKANAN DAN FRAKSI VOLUME PADA HYBRID COMPOSITE SERAT SABUT KELAPA DAN SERAT BAMBU BERMATRIKS RESIN POLYESTER TERHADAP KEKUATAN TARIK DAN BENDING - Febryan Utama Putra; Fajar Paundra; Abdul Muhyi; Fuad Hakim; Lukman Triawan; Abdul Aziz (LPPM Politeknik Manufaktur Ceper, 2023)
Composite is a material that is formed from a combination of two or more constituent materials with a heterogeneous mixing process, which has different mechanical properties. This study aims to determine the effect of volume fraction and molding pressure of composite materials on tensile and bending strength. The volume fractions used are SK 25% & SB 5%, SK 20% & SB 10%, SK 15% & SB 15%, SK 10% & SB 20%, and SK 5% & SB 25%. Each change in printing pressure is carried out at a pressure of 60 bar, 70 bar and 80 bar. Composite testing was carried out using ASTM D3039 for tensile testing and ASTM D790 for bending testing. The results obtained are the highest tensile strength at E3 with a value of 23.573 MPa and the lowest tensile strength at C1 with a value of 9.199 MPa, then the highest bending strength at E2 with a value of 38.665 MPa and the lowest bending strength at B1 with a value of 30.318 MPa.